Translation with cultural adaptation to Portuguese and assessment of the repeatability of the Questionnaire on respiratory symptoms in preschool children - Carvalho,Susana (2014)
Background: Asthma is a very common feature in childhood. The development of questionnaires on respiratory symptoms in Portuguese for children under 3 years old will allow not only a more accurate knowledge of infantile asthma and recurrent wheezing but also the standardization of methodologies to develop nationwide strategies. Objectives: The aim of this study was to select a questionnaire on respiratory symptoms for children under 3 years old, translate it and adapt to the Portuguese culture and determine its repeatability. Methods: The selected questionnaire was the Questionnaire on respiratory symptoms in preschool children by Strippoli et al (2007). The translation was done using the translation and back-translation method, with cultural adaptation. The repeatability of the Portuguese version was assessed with the testretest analyses, by applying the questionnaires to the parents of children between 12 and 36 months old in two phases with an interval of two to four weeks. Results: The response rates were 41% (180/74) in the first phase and 66% (70/46) in the second phase. For test-retest analyses, were included the 41 children with the same respondent (mother, father or legal representative) in both occasions. The median age of the children was 22,5 months, with a predominance of girls (F:M = 1:0,6). The median time between the fillings of both questionnaires was 26 days. Globally, agreement values were good to excellent, similarly to the original work: excellent agreement in 46 items, good agreement in 25 items, moderate agreement in 8 items and low agreement in 2 items. Conclusion: The Questionnaire on respiratory symptoms in preschool children is a questionnaire for self-administration by parents of children under 3 years old, for epidemiological studies and community-based screening programs. It was translated to Portuguese with cultural adaptation, and its repeatability was assessed, with agreement values globally good to excellent, similarly to the original work. The questions that had low agreement have to be either reformulated or excluded.